Effects of a special continuous quality improvement in nursing on the management of adverse care events: a retrospective study - Qing Ouyang; Guixiang Zhang; Ying Xie; Hongman Yuan; Fangqun Cheng; Qiyun Huang (BMC, 2024)
Abstract Objective To explore the application effect of the direct reporting system of adverse nursing events and special continuous nursing quality improvement measures in the management of these adverse events. Methods The implementation time of continuous nursing improvement based on the direct reporting system was the demarcation point. We retrospectively collected and analyzed nursing adverse event reports and hospitalization data from Xiangtan Central Hospital before implementation (2015-2018) and after implementation (2019-2022). The active reporting rate of adverse events, the composition of these events and the processing time were compared between the two groups. Results The rate of active reporting of adverse events before the implementation was lower than that after the implementation (6.7% vs. 8.1%, X 2  = 25.561, P < 0.001). After the implementation of the direct reporting system for nursing events and the continuous improvement of nursing quality, the reporting proportion of first-level and second-level events decreased significantly. Moreover, the reporting proportion of third-level events increased significantly. The proportion of falls and medication errors decreased, and the proportion of unplanned extubation, infusion xerostomia and improper operation increased. The processing time of the reported nursing adverse events was significantly reduced (31.87 ± 7.83 vs. 56.87 ± 8.21, t = 18.73, P < 0.001). Conclusion The direct reporting system of adverse nursing events and the continuous improvement measures for nursing quality can effectively improve the active reporting rate of adverse events, change their composition and reduce their processing time, as well as help create a safe psychological environment for both patients and nursing staff.